Non-invasive chemogenetics. (July 2018) - Menard, Caroline; Russo, Scott
A technique combining focused ultrasound for opening the blood–brain barrier and virally encoded engineered G-protein-coupled receptors for promoting the expression of a gene targeting excitatory neurons enables the non-invasive stimulation of specific brain regions and cell types in mice.